Implementasi Metode Design Thinking dalam Desain User Interface pada Sistem Informasi Berbasis Website - Anggraeni, Motika Dian; Rony, Muhammad Ainur; Saputra, Agung (TIN: Terapan Informatika Nusantara, 2025)
This study aims to design a website user interface for operators of children’s course institutions using the Design Thinking approach. This approach was chosen to gain a deep understanding of user needs and to create a design focused on ease of use and efficiency. The process begins with empathize, which involves deeply understanding users’ needs, emotions, and perspectives through observation and interviews. Next, the define stage aims to formulate the core problem based on empathy findings so that the solution focus becomes more accurate. The ideate stage then encourages the exploration of unlimited creative ideas to discover various possible solutions. These ideas are realized in the prototype stage, where concepts are transformed into tangible forms or simple representations that can be tested. Finally, the test stage is carried out to obtain direct user feedback so that the solution can be refined and made truly relevant to their needs. The evaluation was conducted using the System Usability Scale (SUS) method with ten course operator respondents. The test results showed an average score of 82.5, which falls into the Excellent category, indicating that the designed interface is easy to use, efficient, and satisfying for users. Thus, the application of Design Thinking proved effective in producing an interface design that meets user needs and can serve as a reference for developing similar information systems.